Economics of Thai koi (climbing perch, Anabas testudineus) farming in pond in Bangladesh - Sarker, Md. Al Amin; Mohamed Arshad, Fatimah; Alam, Md. Ferdous; Mohamed, Zainal Abidin; Khan, Md. Akhtaruzzaman (Asian Network for Scientific Information, 2014)
With the high growth and productivity, Thai koi has opened up a new horizon of pond culture in Bangladesh. However, its growth varied widely year to year causing fluctuations in production. This study was undertaken to explore the farm insight practices in an economic viewpoint by framing a total of 149 farmers from Mymensingh district in Bangladesh. The study analyzed the farm profitability and other farming practices based on a per hectare basis for the three feed categories and determine the feed contribution to production. Among variables, feed alone experienced 73% of the gross production costs, implies a greater influence of feed on production. Though, the gross cost was higher, hence, the cost of producing per kg fish was the lowest for the floating feed. The farm income also varied with the variation of input costs among the feed brands and the performance of floating feed was found to be outstanding. Furthermore, floating feed yielded the best performances in terms of feed conversion ratio or daily mean weight gain of fish. Although, the initial investment is higher with the floating, feed farmers can earn much additional returns from the extra investment compared to other feed technologies. Generally, with an average revenue of fish was US$ 1.59 kg-1 and cost of US$ 1.38 kg-1, Thai koi production is considered to be a profitable agri-business. Finally, the outlook for the Thai koi farming could be very optimistic in filling the upcoming demand of fish, thus greatly improved human nutrition and food security by removing the problems and constraints are identified.